Web-based machinability handbook for metal cutting data selection. (1st January 2003) - Wong, S.V.; Putra, A.M.S. Hamouda
This article is devoted to the development and implementation of a web-based fuzzy expert system (FES) for machinability data selection. The FES has been developed using object oriented programming, dynamic link library (DLL) and Axtive-X Control. It can be easily incorporated into internet and intranet environments and can be accessed virtually from any place. A simplified fuzzy set-handling object has been developed in order to save resources. A weighted-centroid rather than a union centroid has been used in output defuzzification. Comparison between these two methods is also made and discussed.